The Contribution of al-Sya'rawi to the Development of Tafsir: Study on the Book of Tafsir al-Sya’rawi - Mhd. Idris (Tamaddun, 2020)
This research discusses the contribution of Imam al-Sya’rawi in the field of interpretation with his phenomenal work Tafsir al-Sya’rawi. This article aims to find out about the general profile of the author of the Tafsir al-Sya’rawi, the background of the tafsir, the method, and style of interpretation as well as the strengths and weaknesses of this Sya'rawi's interpretation. This research is library research that is descriptive-analytical. The primary source used is the book of Tafsir al-Sya'rawi and literature related to this discussion as secondary sources. The results showed that the book of Tafsir al-Sya’rawi was the work of a prominent scholar from Egypt named Sheikh Muhammad Mutawally al-Sya`râwi, born in 1911 in Egypt. The name of Tafsir al-Sya’rawi is taken from the original name of the writer. This interpretation uses the tahlili method and is characterized by al-adab al-ijtima’i. This interpretation is presented with nuances that are in direct contact with social themes, through a fairly simple language technique. But the drawback is that there is no reference source when quoting the opinions of other scholars and there is no assessment of the quality of the hadiths quoted.Penelitian ini membahas tentang kontribusi Imam Sya’rawi di bidang tafsir dengan karya fenomenalnya Tafsir al-Sya`rawi. Tulisan ini bertujuan untuk mengetahui tentang profil umum penulis Tafsir Sya'rawi, latar belakang tafsir, cara dan gaya tafsir, serta kekuatan dan kelemahan Tafsir al-Sya’rawi ini. Penelitian ini merupakan penelitian pustaka yang bersifat deskriptif-analitik. Sumber primer yang digunakan adalah kitab Tafsir al-Sya’rawi dan literatur terkait pembahasan ini sebagai sumber sekunder. Hasil penelitian menunjukkan bahwa kitab Tafsir al-Sya’rawi merupakan karya seorang ulama terkemuka dari Mesir bernama Syekh Muhammad Mutawally al-Sya`râwi, lahir pada tahun 1911 di Mesir. Nama Tafsir al-Sya’rawi diambil dari nama asli penulisnya. Tafsir ini menggunakan metode tahlili dan bercirikan al-adab al-ijtima’i. Interpretasi ini dihadirkan dengan nuansa yang bersentuhan langsung dengan tema sosial, melalui teknik bahasa yang cukup sederhana. Tetapi kekurangannya adalah tidak ada sumber referensi ketika mengutip pendapat ulama lain dan tidak ada penilaian kualitas hadits yang dikutip.